Prevalence of human brucellosis in the slaughterhouse and cattle fair of Medellín - Tenorio M., Carlos Alberto; Velásquez A., Elmer (Medicina UPB, 1986)
One hundred and eighty six employers of the slaughterhouse and livestock market of city of Medellin (Colombia) were examined looking for the prevalence of Brucellosis. The diagnosis was based in the presence of levels higher than 1: 50 in Bang test, in tube test and 2-Mercaptoethanol in those patients with clinic symptoms compatible with brucellosis. Only one positive case was found and there three suspected cases. Due to this, no significant relation could be stablished between the illness and other factors as symptom, work, time of exposition or personal antecedents. This low prevalence in human (0.5%) seems to reflect the prevalence of brucellosis in bovines from the zones that supply the city of Medellin.
Keywords: Human Brucellosis; Ocupational high risk; 2-Mercaptoethanol